2016
DOI: 10.1111/1467-6427.12113
|View full text |Cite
|
Sign up to set email alerts
|

Couple emotional experience: effects of attachment anxiety in low and high structure couple interactions

Abstract: This study used data from 63 heterosexual couples to investigate the effects of attachment anxiety and how they relate to emotional experience (i.e. psychophysiological distress and feelings towards a partner) in the context of two therapy‐like conditions (low and high structure). We examined both the effect of an individual's anxiety on his/her own emotional experience (actor effects) and on the partner's experience (partner effects). During both interactional conditions, female partners of men higher in atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Consistent with previous studies using skin conductance, there were no statistically significant actor effects between attachment anxiety and psychophysiological arousal, despite emotional arousal being a common manifestation of attachment anxiety (Mikulincer & Shaver, ). Previous studies using skin conductance have reported partner effects, where female partners of men with high levels of attachment anxiety had higher levels of psychophysiological arousal during positive and conflict interactions (Seedall & Lachmar, ; Seedall & Wampler, ). This finding was only replicated in the final third of the conflict discussion, although the partner effects were nearing significance in other segments of conflict and recovery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous studies using skin conductance, there were no statistically significant actor effects between attachment anxiety and psychophysiological arousal, despite emotional arousal being a common manifestation of attachment anxiety (Mikulincer & Shaver, ). Previous studies using skin conductance have reported partner effects, where female partners of men with high levels of attachment anxiety had higher levels of psychophysiological arousal during positive and conflict interactions (Seedall & Lachmar, ; Seedall & Wampler, ). This finding was only replicated in the final third of the conflict discussion, although the partner effects were nearing significance in other segments of conflict and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Seedall and Wampler () hypothesized that the fears of abandonment and relationship worry that typically accompany attachment anxiety may be more general and not fully activated during couple conflict. In other words, those high in attachment anxiety may be able to focus on some interactional tasks without it activating their relationship fears or worry.…”
Section: Attachment Theory and Close Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations